Effects of surface instability on cortical information processing during multi- joint compound movements: an exploratory EEG study - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Performance and Brain Activity in Older Adults while Playing Leaning and Stepping Exergames - Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Ecological validity in exercise neuroscience research: A systematic investigation - Chang, Melissa; Büchel, Daniel; Reinecke, Kirsten; Lehmann, Tim; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Motorische Kompetenzen im Kindesalter: Monitoring, Intervention und Zusammenhänge mit der Selbstwahrnehmung - Strotmeyer, Anne
Motorische Kompetenzen und die Selbstwahrnehmung dieser sind zentral hinsichtlich der Ausbildung eines gesundheitsförderlichen Lebensstils. Bewegungsmangel im Kindesalter und motorische Defizite unterstreichen die Relevanz von Untersuchungen in diesem Forschungsfeld. In diesem Kontext besteht Forschungsbedarf, welcher an der jungen Forschungslinie zu motorischen Basiskompetenzen ansetzt. Daher zielt die vorliegende Arbeit auf die Untersuchung motorischer Basiskompetenzen im Kontext des Monitorings, der Intervention sowie der Untersuchung von Zusammenhängen mit der Selbstwahrnehmung. Es wurden konfirmatorische Faktorenanalysen durchgeführt sowie eine kompetenzorientierte Intervention für das mittlere Kindesalter konzipiert und evaluiert. Zudem fanden Varianzanalysen mit Messwiederholung und manifeste Pfadmodelle Anwendung. Neben der Bestätigung der faktoriellen Struktur des Tests zur Erfassung motorischer Basiskompetenzen (MOBAK 3-4), wurden Zusammenhänge mit endogenen sowie exogenen Faktoren nachgewiesen. Es konnte gezeigt werden, dass mit Hilfe der relativ kurzen Intervention positive Effekte auf die motorischen Basiskompetenzen erzielt werden können. Zudem zeigten sich moderate Korrelationen zwischen motorischen Basiskompetenzen und der Selbstwahrnehmung. Auf Grundlage dieser Befunde sollten im Bereich der Objektkontrolle vor allem motorische Kompetenzen und im Bereich der Lokomotion insbesondere die Selbstwahrnehmung zur Steigerung des Kompetenzlevels gefördert werden.

COVID-19 in German Competitive Sports: Protocol for a Prospective Multicenter Cohort Study (CoSmo-S) - Niess, Andreas Michael; Widmann, Manuel; Gaidai, Roman; Gölz, Christian Johannes; Schubert, Isabel; Castillo, Katty; Sachs, Jan Philipp; Bizjak, Daniel; Vollrath, Shirin; Wimbauer, Fritz; Vogel, Azin; Keller, Karsten; et al. (International Journal of Public Health)
Objective: It is unclear whether and to what extent COVID-19 infection poses health risks and a chronic impairment of performance in athletes. Identification of individual health risk is an important decision-making basis for managing the pandemic risk of infection with SARS-CoV-2 in sports and return to play (RTP). Methods: This study aims 1) to analyze the longitudinal rate of seroprevalence of SARS-CoV-2 in German athletes, 2) to assess health-related consequences in athletes infected with SARS-CoV-2, and 3) to reveal effects of the COVID-19 pandemic in general and of a cleared SARS-CoV-2 infection on exercise performance. CoSmo-S is a prospective observational multicenter study establishing two cohorts: 1) athletes diagnosed positive for COVID-19 (cohort 1) and 2) federal squad athletes who perform their annual sports medical preparticipation screening (cohort 2). Comprehensive diagnostics including physical examination, laboratory blood analyses and blood biobanking, resting and exercise electrocardiogram (ECG), echocardiography, spirometry and exercise testing added by questionnaires are conducted at baseline and follow-up. Results and Conclusion: We expect that the results obtained, will allow us to formulate recommendations regarding RTP on a more evidence-based level.
Keywords: Public Health; Environmental and Occupational Health; Health (social science)

Stimulating performance: A scoping review on transcranial electrical stimulation effects on olympic sports - Friehs, Maximilian A.; Whelan, Eric; Güldenpenning, Iris; Krause, Daniel; Weigelt, Matthias (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Valence-dependent neural correlates of augmented feedback processing in extensive motor sequence learning – Part II: Predictive value of event-related potentials for behavioral adaptation and learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (Neuroscience)
Keywords: General Neuroscience

Valence-dependent Neural Correlates of Augmented Feedback Processing in Extensive Motor Sequence Learning – Part I: Practice-related Changes of Feedback Processing - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (Neuroscience)
Keywords: General Neuroscience

Repeating head fakes in basketball: Temporal aspects affect the congruency sequence effect and the size of the head-fake effect. - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Journal of Experimental Psychology: Applied)
Keywords: Experimental and Cognitive Psychology

Examining the Neural Processes of Valence-Dependent Feedback Processing and Practice-Related Changes in Extensive Motor Learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Surprising effects of frontal neural correlates of augmented feedback-processing in extensive motor learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Professionswissen von angehenden Sportlehrkräften zur Gestaltung ei-nes bewegungsorientierten Schulalltags. Eine empirische Untersuchung im Bereich des Professionswissens von Lehrpersonen. - Satzinger, Nicole
Forschungsarbeiten zum Professionswissen von Sportlehrer*innen beschränkt sich weitgehend auf den Sportunterricht. Dem außerunterrichtlichen Schulsport wurde bisher wenig Aufmerksamkeit geschenkt. Hier setzt die vorliegende Arbeit an, die sich auf das Professionswissen von Sportlehrer*innen zur Gestaltung eines bewegungsorientierten Schulalltags konzentriert. Als theoretische Rahmung liegen den Überlegungen das Kompetenzmodell von Baumert und Kunter (2011) und das Zahnradmodell der "Bewegten Schule" von Städler (2016) zugrunde. Die empirische Untersuchung basiert auf einem dreistufigen Vorgehen. Zuerst wurde im Rahmen von fünf Fokusgruppeninterviews mit Expert*innen die aus Praxissicht relevanten Wissensfacetten des Professionswissens zur Gestaltung eines bewegungsorientierten Schulalltags erhoben. Die Auswertung erfolgte auf Basis der qualitativen Inhaltsanalyse nach Mayring (2015). Darauf aufbauend wurden die Facetten in einer Fragebogenerhebung von Expert*innen hinsichtlich ihrer jeweiligen Relevanz bewertet, anschließend wurden die Ergebnisse bilanzierend zusammengeführt. Es konnten 46 Wissensfacetten des Professionswissens identifiziert werden, die in 11 übergreifenden Kategorien geclustert wurden. Die Bereiche des Professionswissens nach Baumert und Kunter (2011) werden vollständig abgebildet und eine Zuordnung dem Zahnradmodell von Städler (2016) fand statt. Ein Professionswissen im Bereich Organisation und Beratung scheint relevant zur Gestaltung eines bewegungsorientierten Schulalltags zu sein. Die Erkenntnisse können als Ansatzpunkt für Forschungsarbeiten sowie für die universitäre Ausbildung dienen.
Keywords: Professionswissen; Sportlehrerausbildung

A longitudinal analysis of reciprocal relationships between actual and perceived motor competencies and physical self-concept in primary-school age children - Strotmeyer, Anne; Herrmann, Christian; Kehne, Miriam (Psychology of Sport and Exercise)
Physical self-concept (PSC) and motor competencies are important factors in view of the development of a physically active lifestyle. There are research gaps regarding longitudinal studies of these relationships. This article presents findings of a longitudinal study (n = 200; 58% girls, M = 8.84 ± 0.63 years) at three primary schools. The aim of this study was to analyze the relationship between actual motor competencies (AMC) and perceived motor competencies (PMC) and PSC. Therefore, manifest path models in cross-lagged design were performed. Results show that correlations between PMC and AMC increased over time and were stronger in object control than in locomotor. Effects of AMC on PSC were more strongly mediated by PMC in object control than in locomotor. To promote physical activity, developing strategies should be aimed at the acquisition of AMC, particularly in object control, and PMC, especially in locomotor, during childhood.
Keywords: Applied Psychology

Gesundheit und Stress im Studium - Bedeutung gesundheitsrelevanter Lebensstile - Waltert, Carolin

Die ausgekugelte Schulter im Kanusport. Behandlung und Vorbeugen - Bauer, A.; Buhmann, H. W.; Güldenpenning, Iris (Kanusport)

Produktionskosten von Täuschungshandlungen im Sport: Der Einfluss von Übung auf die Durchführung von Blicktäuschungen im Basketball - Böer, Nils Tobias; Weigelt, Matthias; Schütz, Christoph; Güldenpenning, Iris (Ein Gehirn, viel Bewegung – Variabilität und Plastizität über die Lebensspanne. Abstractband der 54. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Producing deceptive actions in sports: The costs of generating head fakes in basketball - Böer, Nils Tobias; Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (Abstracts of the 64th Conference of Experimental Psychologists (TeaP))

Kognitive Grundlagen von Täuschungshandlungen im Sport - Weigelt, Matthias; Güldenpenning, Iris (Kognition und Motorik: Sportpsychologische Grundlagen und Anwendungen im Sport)

Das Stützpunktsystem im paralympischen Leistungssport. Eine empirische Studie unter Berücksichtigung der Perspektive von Para-Athletinnen und -Athleten sowie des Stützpunktpersonals. - Radtke, Sabine; Freier, M. Pia
Keywords: Para Sport

Betriebliche Gesundheitsförderung: Ein leeres Versprechen? - Auer, Thorsten Fabian; Sennefelder, Lisa; Meier, Heiko (Public Health Forum)
Unternehmen investieren zunehmend in Angebote Betrieblicher Gesundheitsförderung (BGF). Dabei stellt sich die Frage nach dem Kosten-Nutzen-Verhältnis jenseits des individuellen Nutzens durch die Förderung der Mitarbeitergesundheit. Deshalb wurden im Rahmen einer Sekundäranalyse Effekte der BGF auf den Unternehmenserfolg berechnet. Die Ergebnisse lassen vermuten, dass sich eine verhaltensorientierte BGF kaum positiv auf die Arbeitsproduktivität und Kommunikationsstruktur in Unternehmen auswirkt.
Keywords: Kommunikation; Arbeitsproduktivität; Betriebliche Gesundheitsförderung; Kosten-Nutzen-Verhältnis

Editorial: Netzwerke und Vernetzung im Sport - Meier, Heiko; Kukuk, Marc; Riedl, Lars (Sport und Gesellschaft)
Keywords: Philosophy; Social Sciences (miscellaneous); History

Vereinzelung oder Gemeinschaftsbildung: Was passiert an Calisthenics-Anlagen? - Meier, Heiko; Kukuk, Marc; Schmieding, Ruben (Playground@Landscape)

Die Bedeutung und Funktion sportlicher Aktivitäten im Gesundheitsmanagement der öffentlichen Verwaltungen - Barrieren und Gelingensbedingungen. - Sennefelder, Lisa

Wie passen Vertrauen, Kontrolle und Hierarchie zusammen? Ein erlebnispädagogisch orientiertes Konzept zum Aufbau einer Vertrauenskultur in Verwaltungsorganisationen - Sennefelder, Lisa; Meier, Heiko

Vertrauen im Sport – mehr als nur ein No-Look-Pass - Meier, Heiko (Facetten des Vertrauens und Misstrauens)
Ohne ständig thematisiert zu werden, kommt Vertrauen im Sport immer eine große Bedeutung zu, sei es beim No-look-Pass, bei der Hilfestellung im Turnen oder im Klettersport. Mehr noch: Ohne Vertrauensgrundlage ist Sport praktisch oftmals unmöglich. Umgekehrt wiegen Vertrauensbrüche schwer. Sie gefährden Sportarten, Sportorganisationen und Personen. Damit ist der Aufbau von Vertrauen offensichtlich für den Sport konstitutiv. Der Beitrag untersucht deshalb, wie Vertrauen im Sport nicht nur soziale Verhältnisse und Beziehungen umrahmt, sondern sie konstituiert, und inwiefern sich der Sport diesbezüglich von anderen gesellschaftlichen Kontexten unterscheidet. Dazu wird unter Rückgriff auf Niklas Luhmanns Unterscheidung zwischen Person- und Systemvertrauen der Sportverein dahingehend analysiert, wie bedeutsam und wie funktional Vertrauen für dessen Selbstorganisation und Systemerhalt ist. Dies führt zu dem Vorschlag, Vertrauen im Sportverein als Steuerungsinstrument anzusehen, welches in einer spezifischen Symbolik zum Ausdruck kommt.

"Und dann muss es gelebt werden!" - Der Sport im Gesundheitsmanagement öffentlicher Verwaltungen - Sennefelder, Lisa

Vertrauen in der öffentlichen Verwaltung - Sennefelder, Lisa

Exploring intensity-dependent modulations in EEG resting-state network efficiency induced by exercise - Büchel, Daniel; Sandbakk, Øyvind; Baumeister, Jochen (European Journal of Applied Physiology)
Abstract Purpose Exhaustive cardiovascular load can affect neural processing and is associated with decreases in sensorimotor performance. The purpose of this study was to explore intensity-dependent modulations in brain network efficiency in response to treadmill running assessed from resting-state electroencephalography (EEG) measures. Methods Sixteen trained participants were tested for individual peak oxygen uptake (VO 2 peak ) and performed an incremental treadmill exercise at 50% (10 min), 70% (10 min) and 90% speed VO 2 peak (all-out) followed by cool-down running and active recovery. Before the experiment and after each stage, borg scale (BS), blood lactate concentration (B La ), resting heartrate (HR rest ) and 64-channel EEG resting state were assessed. To analyze network efficiency, graph theory was applied to derive small world index (SWI) from EEG data in theta, alpha-1 and alpha-2 frequency bands. Results Analysis of variance for repeated measures revealed significant main effects for intensity on BS, B La , HR rest and SWI. While BS, B La and HR rest indicated maxima after all-out, SWI showed a reduction in the theta network after all-out. Conclusion Our explorative approach suggests intensity-dependent modulations of resting-state brain networks, since exhaustive exercise temporarily reduces brain network efficiency. Resting-state network assessment may prospectively play a role in training monitoring by displaying the readiness and efficiency of the central nervous system in different training situations.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.

EEG-derived brain graphs are reliable measures for exploring exercise-induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Abstract The interaction of acute exercise and the central nervous system evokes increasing interest in interdisciplinary research fields of neuroscience. Novel approaches allow to monitor large-scale brain networks from mobile electroencephalography (EEG) applying graph theory, but it is yet uncertain whether brain graphs extracted after exercise are reliable. We therefore aimed to investigate brain graph reliability extracted from resting state EEG data before and after submaximal exercise twice within one week in male participants. To obtain graph measures, we extracted global small-world-index (SWI), clustering coefficient (CC) and characteristic path length (PL) based on weighted phase leg index (wPLI) and spectral coherence (Coh) calculation. For reliability analysis, Intraclass-Correlation-Coefficient (ICC) and Coefficient of Variation (CoV) were computed for graph measures before (REST) and after POST) exercise. Overall results revealed poor to excellent measures at PRE and good to excellent ICCs at POST in the theta, alpha-1 and alpha-2, beta-1 and beta-2 frequency band. Based on bootstrap-analysis, a positive effect of exercise on reliability of wPLI based measures was observed, while exercise induced a negative effect on reliability of Coh-based graph measures. Findings indicate that brain graphs are a reliable tool to analyze brain networks in exercise contexts, which might be related to the neuroregulating effect of exercise inducing functional connections within the connectome. Relative and absolute reliability demonstrated good to excellent reliability after exercise. Chosen graph measures may not only allow analysis of acute, but also longitudinal studies in exercise-scientific contexts.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)

Mentale Rotationsleistungen bei der Betrachtung und Umsetzung von Spielzügen im Basketball: Novizen vs. erfahrene Basketballspieler - Krause, Daniel; Behrens, J.B.; Löhers, L.; Weigelt, Matthias

Representations after mentally practiced one finger sequences are effector independent - Dahm, Stephan; Weigelt, Matthias; Rieger, M.

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing - Budde, Kirsten; Barela, J.A.; Figueiredo, G.A.; Weigelt, Matthias

How does spectator presence affect football? Home advantage remains in European top-class football matches played without spectators during the COVID-19 pandemic - Wunderlich, Fabian; Weigelt, Matthias; Rein, Robert; Memmert, Daniel (PLOS ONE)
The present paper investigates factors contributing to the home advantage, by using the exceptional opportunity to study professional football matches played in the absence of spectators due to the COVID-19 pandemic in 2020. More than 40,000 matches before and during the pandemic, including more than 1,000 professional matches without spectators across the main European football leagues, have been analyzed. Results support the notion of a crowd-induced referee bias as the increased sanctioning of away teams disappears in the absence of spectators with regard to fouls (p < .001), yellow cards (p < .001), and red cards (p < .05). Moreover, the match dominance of home teams decreases significantly as indicated by shots (p < .001) and shots on target (p < .01). In terms of the home advantage itself, surprisingly, only a non-significant decrease is found. While the present paper supports prior research with regard to a crowd-induced referee bias, spectators thus do not seem to be the main driving factor of the home advantage. Results from amateur football, being naturally played in absence of a crowd, provide further evidence that the home advantage is predominantly caused by factors not directly or indirectly attributable to a noteworthy number of spectators.
Keywords: Multidisciplinary

Mental body rotation with egocentric and object-based transformations in different postures: standing vs. balancing - Budde, Kirsten; Jöllenbeck, Thomas; Barela, José A.; Figueiredo, Gabriella A.; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: Previous studies suggest better visual-spatial processing when participants are tested in postures in which dynamic stability is challenged. The question arises if this is also true for the performance in mental body-rotation tasks (MBRT). AIM: Taking the embodied cognition approach into account, the first aim of the present study was to examine the potential influence of different demands on dynamic stability for two postures (parallel stand vs. tandem stand) on solving two versions of the MBRT, inducing either an object-based or an egocentric perspective transformation strategy. The second aim was to investigate if these different demands on dynamic stability are reflected in postural sway parameters. METHOD: Thirty participants (18 females and 12 males) were tested in the two MBRTs and in a control condition. All tasks were performed while standing on a balance beam in tandem stand and in a feet parallel position on a force plate. RESULTS: The results for response time and response error revealed effects of rotation angle and task, but no effect of posture. The analyzed Center of Pressure (CoP) data revealed a reduction of body sway during the MBRT for egocentric perspective transformations. CONCLUSION: The results indicate that participants performed better for egocentric than for object-based transformations and that the egocentric transformation leads to more postural stability than the object-based.
Keywords: General Engineering

Neurophysiology of embodied mental rotation: Event‐related potentials in a mental rotation task with human bodies as compared to alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias (European Journal of Neuroscience)
Keywords: General Neuroscience

An interrater reliability study of gait analysis systems with the dual task paradigm in healthy young and older adults - Klotzbier, Thomas Jürgen; Wollesen, Bettina; Vogel, Oliver; Rudisch, Julian; Cordes, Thomas; Jöllenbeck, Thomas; Vogt, Lutz (European Review of Aging and Physical Activity)
Abstract Background and aims One reason for the controversial discussion of whether the dual task (DT) walking paradigm has an added value for diagnosis in clinical conditions might be the use of different gait measurement systems. Therefore, the purpose was 1) to detect DT effects of central gait parameters obtained from five different gait analysis devices in young and old adults, 2) to assess the consistency of the measurement systems, and 3) to determine if the absolut and proportional DT costs (DTC) are greater than the system-measurement error under ST. Methods Twelve old (72.2 ± 7.9y) and 14 young adults (28.3 ± 6.2y) walked a 14.7-m distance under ST and DT at a self-selected gait velocity. Interrater reliability, precision of the measurement and sensitivity to change were calculated under ST and DT. Results An age effect was observed in almost all gait parameters for the ST condition. For DT only differences for stride length ( p < .029, ɳ 2 p = .239) as well as single and double limb support ( p = .036, ɳ 2 p = .227; p = .034, ɳ 2 p = .218) remained. The measurement systems showed a lower absolute agreement compared to consistency across all systems. Conclusions When reporting DT effects, the real changes in performance and random measurement errors should always be accounted for. These findings have strong implications for interpreting DT effects.
Keywords: Geriatrics and Gerontology

Agreement and consistency of five different clinical gait analysis systems in the assessment of spatiotemporal gait parameters - Rudisch, Julian; Jöllenbeck, Thomas; Vogt, Lutz; Cordes, Thomas; Klotzbier, Thomas Jürgen; Vogel, Oliver; Wollesen, Bettina (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Learning to play golf for elderly people with subjective memory complaints: feasibility of a single‐blinded randomized pilot trial - Stroehlein, Julia K.; Vieluf, Solveig; Zimmer, Philipp; Schenk, Alexander; Oberste, Max; Gölz, Christian Johannes; van den Bongard, Franziska; Reinsberger, Claus (BMC Neurology)
Abstract Background Subjective Memory Complaints (SMC) in elderly people due to preclinical Alzheimer’s Disease may be associated with dysregulation of the Kynurenine Pathway (KP), with an increase in neurotoxic metabolites that affect cognition. Golf is a challenging sport with high demands on motor, sensory, and cognitive abilities, which might bear the potential to attenuate the pathological changes of preclinical AD. This trial investigated the feasibility of learning to play golf for elderly with cognitive problems and its effects on cognitive functions and the KP. Methods In a 22-week single-blinded randomized controlled trial, elderly people with SMC were allocated to the golf ( n = 25, 180 min training/week) or control group ( n = 21). Primary outcomes were feasibility (golf exam, adherence, adverse events) and general cognitive function (Alzheimer’s Disease Assessment Scale). Secondary outcomes include specific cognitive functions (Response Inhibition, Corsi Block Tapping Test, Trail Making Test), KP metabolites and physical performance (6-Minute-Walk-Test). Baseline-adjusted Analysis-of-Covariance was conducted for each outcome. Results 42 participants were analyzed. All participants that underwent the golf exam after the intervention passed it (20/23). Attendance rate of the golf intervention was 75 %. No adverse events or drop-outs related to the intervention occurred. A significant time*group interaction ( p = 0.012, F = 7.050, Cohen’s d = 0.89) was found for correct responses on the Response Inhibition task, but not for ADAS-Cog. Moreover, a significant time*group interaction for Quinolinic acid to Tryptophan ratios ( p = 0.022, F = 5.769, Cohen’s d = 0.84) in favor of the golf group was observed. An uncorrected negative correlation between attendance rate and delta Quinolinic acid to Kynurenic acid ratios in the golf group ( p = 0.039, r =-0.443) was found as well. Conclusions The findings indicate that learning golf is feasible and safe for elderly people with cognitive problems. Preliminary results suggest positive effects on attention and the KP. To explore the whole potential of golfing and its effect on cognitive decline, a larger cohort should be studied over a longer period with higher cardiovascular demands. Trial registration The trial was retrospectively registered (2nd July 2018) at the German Clinical Trials Register ( DRKS00014921 ).
Keywords: Clinical Neurology; General Medicine

Generalized tonic-clonic seizures are accompanied by changes of interrelations within the autonomic nervous system. - Vieluf, S; Hasija, Tanuj; Schreier, PJ; El Atrache, R; Hammond, S; Mohammadpour Touserkani, F; Sarkis, RA; Loddenkemper, T; Reinsberger, Claus (Epilepsy Behav)

Electrophysiological signatures of dedifferentiation differ between fit and less fit older adults - Gölz, Christian Johannes; Mora, Karin; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Dellnitz, Michael; Reinsberger, Claus; Vieluf, Solveig (Cognitive Neurodynamics)
Abstract Cardiorespiratory fitness was found to influence age-related changes of resting state brain network organization. However, the influence on dedifferentiated involvement of wider and more unspecialized brain regions during task completion is barely understood. We analyzed EEG data recorded during rest and different tasks (sensory, motor, cognitive) with dynamic mode decomposition, which accounts for topological characteristics as well as temporal dynamics of brain networks. As a main feature the dominant spatio-temporal EEG pattern was extracted in multiple frequency bands per participant. To deduce a pattern’s stability, we calculated its proportion of total variance among all activation patterns over time for each task. By comparing fit (N = 15) and less fit older adults (N = 16) characterized by their performance on a 6-min walking test, we found signs of a lower task specificity of the obtained network features for the less fit compared to the fit group. This was indicated by fewer significant differences between tasks in the theta and high beta frequency band in the less fit group. Repeated measures ANOVA revealed that a significantly lower proportion of total variance can be explained by the main pattern in high beta frequency range for the less fit compared to the fit group [F(1,29) = 12.572, p = .001, partial η 2 = .300]. Our results indicate that the dedifferentiation in task-related brain activation is lower in fit compared to less fit older adults. Thus, our study supports the idea that cardiorespiratory fitness influences task-related brain network organization in different task domains.
Keywords: Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Gaidai, Roman; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Goelz, C.; Mora, K.; Rudisch, J.; Gaidai, R.; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Twenty-four-hour patterns in electrodermal activity recordings of patients with and without epileptic seizures. - Vieluf, S; Amengual-Gual, M; Zhang, B; El Atrache, R; Ufongene, C; Jackson, MC; Branch, S; Reinsberger, Claus; Loddenkemper, T (Epilepsia)

Exercise and sports after COVID-19-Guidance from a clinical perspective. - Halle, M; Bloch, W; Niess, AM; Predel, HG; Reinsberger, Claus; Scharhag, J; Steinacker, J; Wolfarth, B; Scherr, J; Niebauer, J (Transl Sports Med)

The effects of repetitive head impacts on postural control: A systematic review. - Bonke, EM; Southard, J; Buckley, TA; Reinsberger, Claus; Koerte, IK; Howell, DR (J Sci Med Sport)

Head injuries in professional football (soccer): Results of video analysis verified by an accident insurance registry. - Krutsch, V; Krutsch, W; Härtl, J; Bloch, H; Alt, V; Klein, C; Reinsberger, Claus; Seiffert, R; Huber, L; Weber, J (PLoS One)